Exploring ‘endangered living fossils’ (ELFs) among monotypic genera of plants and animals of the world - Vargas, Pablo (Frontiers in Ecology and Evolution, 2023)
The recently proposed concept of ´endangered living fossils’ (ELFs) integrates high-endangered status and evolutionary singularity for any species. In this review, I gathered monotypic genera (single-species genera) that satisfy the three ELF criteria: (i) scarcity and narrow distribution of populations, i.e., considering every species categorized ‘critically endangered’ or contemporary ´extinct´ by IUCN criteria; (ii) evolutionary singularity, i.e., both morphological and phylogenetic singularities of a single-species lineage as a result of a null net diversification rate; and (iii) ancient divergence, i.e., split from the closest extant relatives predating a particular geological epoch. A total of 3,706 monotypic genera of vertebrates and angiosperms were analyzed. I found 109 critically endangered and contemporary extinct genera of which 57 were ELFs. The emergent patterns are: (1) taxonomy (generic level) is a reliable first approach to identifying ELFs; (2) ´morphological singularity´ displayed by monotypic genera does not always help identify ELFs on islands; (3) species of monotypic genera tend to be more threatened than average species; (4) extinction appears to be biased against some animal and plant groups; (5) contemporary extinct genera are strongly associated with distribution on islands, particularly for flightless birds vulnerable to human prosecution; and (6) the ELF approach is a relatively quick method to identify the species of floras and faunas most urgently in need of protection in the world. This approach is complementary to any method searching for phylogenetic diversity (e. g. EDGE), which is also discussed. I argue that ELFs should be prioritized in conservation because they are the most threatened lineages representing an exceptional evolutionary heritage in the world.